2023
DOI: 10.1021/acs.est.3c03165
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidation of Antibiotics by Ferrate Mediated with Natural Organic Matter: Role of Phenolic Moieties

Abstract: The increasing presence of antibiotics in water sources threatens public health and ecosystems. Various treatments have been previously applied to degrade antibiotics, yet their efficiency is commonly hindered by the presence of natural organic matter (NOM) in water. On the contrary, we show here that nine types of NOM and NOM model compounds improved the removal of trimethoprim and sulfamethoxazole by ferrate(VI) (FeVIO4 2–, Fe(VI)) under mild alkaline conditions. This is probably associated with the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…The presence of natural organic matter, especially phenolic organics, in the actual water body normally has a negative impact on the removal of target pollutants. [36] Taking CIP as the target pollutant, our system maintains sufficient removal performance in lake water and in the presence of phenol (Figure S27a), which further confirms the application potential of the system for real water treatment. It is also shown that the photo-self-Fenton system exhibits better degradation performance than that of the photo-Fenton system (with the addition of 120 μM H 2 O 2 , the same concentration of H 2 O 2 produced by panel reactor with TTP).…”
Section: Methodssupporting
confidence: 68%
“…The presence of natural organic matter, especially phenolic organics, in the actual water body normally has a negative impact on the removal of target pollutants. [36] Taking CIP as the target pollutant, our system maintains sufficient removal performance in lake water and in the presence of phenol (Figure S27a), which further confirms the application potential of the system for real water treatment. It is also shown that the photo-self-Fenton system exhibits better degradation performance than that of the photo-Fenton system (with the addition of 120 μM H 2 O 2 , the same concentration of H 2 O 2 produced by panel reactor with TTP).…”
Section: Methodssupporting
confidence: 68%
“…Divalent cations can enhance DOM sorption to the manganese oxide surface via ligand-exchange or cation-bridging mechanisms and could affect phenolic compound kinetics in two ways (Figure S1). First, enhanced sorption of DOM to the manganese oxide surface may block reactive sites from phenolic target compounds because DOM is thought to sorb and react via phenolic moieties; ,, thus, competitive sorption could result in slower removal of the target compound. Second, enhanced DOM sorption to the mineral surface could result in increased oxidation of DOM and an increase in radical intermediates generated when phenolic moieties within DOM react with manganese oxides via a one-electron transfer (i.e., as observed for individual phenols ,,,, ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We further hypothesized that the observed increases in bisphenol A oxidation were driven by interactions between radicals generated when DOM is oxidized by acid birnessite. The reaction of phenols with manganese oxides first generates a phenoxy radical intermediate by a one-electron transfer. ,,,, As DOM is likely oxidized via phenolic moieties, ,, this radical formation is potentially a key intermediate in the DOM oxidation process as well. Previous work has proposed that radical intermediates from oxidized phenols ,, or model compounds indirectly transform organic contaminants, thereby increasing the observed oxidation rate constants of target compounds.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations